A narrative review of intraoperative floppy iris syndrome: an update 2020 - Yang, Xue (Ann Transl Med, 2020)
Intraoperative floppy iris syndrome (IFIS) is characterized by intraoperative floppiness or billowing of the iris, progressive miosis, and iris prolapse through the surgical wounds. It was originally reported about fifteen years ago, which was later identified to be closely associated with tamsulosin, the most commonly used α1 adrenoceptor antagonist for benign prostatic hyperplasia (BPH). A variety of risk factors, including age, gender, hypertension, axial length of the eye, 5α-reductase inhibitors, other α adrenoceptor antagonist and neuromodulators, have been connected with IFIS. If IFIS occurs during phacoemulsification surgery, complications such as corneal endothelial loss, iris trauma, posterior capsule rupture (PCR), high intraocular pressure and vitreous loss are significantly increased. Therefore, preoperative evaluation of high-risk patients and appropriate intraoperative intervention is crucial to avoid severe complications. This review summarizes the pathogenesis and clinical features of classic IFIS, and provides some clinical pearls to ophthalmologists that may help identify, prevent or reduce IFIS associated complications. Additionally, from the perspective of clinical occurrence of IFIS, there are some recommendations for urologists as well. In conclusion, both ophthalmologists and urologists should be aware of this special clinical situation and communicate with each other about their own fields. A multidisciplinary interaction is of importance to simplify potentially complicated clinical issues.